Exploring corporate reputation and crisis communication - Nuortimo, Kalle; Harkonen, Janne; Breznik, Kristijan (Palgrave Macmillan, 2025)
Corporate reputation, the collective perception of company attractiveness towards stakeholders, impacts business outcomes, while effective communication strategies play a critical role in shaping and maintaining the reputation. The role of communication is highlighted during crises, crisis communication being a strategic approach to managing and mitigating the impact of unexpected or adverse events on the reputation, operations, and stakeholders. These concepts are deeply interrelated with interactive marketing. This study explores the dynamics of corporate reputation and crisis communication during a recent global crisis by combining a literature review, opinion mining, and classification analysis. This is because stakeholders rely on various information sources and engage in online discussions, which can impact the reputation, and pose new challenges. The opinion mining analysis draws from the media communication of selected stock-listed companies during a crisis. The key findings shed light on the dynamics of corporate reputation and crisis communication and the impacts on interactive marketing. Critical components of crisis communication are identified to include monitoring, tactics of responding, and response management. Linkages between these, crisis communication theories, and corporate reputation are synthesised. Indications are provided on how the crisis can affect the corporate reputation and the significance of the speed of preventive communication measures.